A conceptual framework for barriers of circular supply chains for sustainability in the textile industry. (22nd July 2020) - Kazancoglu, Ipek; Kazancoglu, Yigit; Yarimoglu, Emel; Kahraman, Aysun
Abstract: Circular economy is a contemporary concept including usage of renewable materials and technologies. The transition to the circular economy creates value through closed‐loop systems, reverse logistics, eco‐design, product life cycle management, and clean production. The aim of the study was to propose a holistic conceptual framework for barriers of circular supply chain for sustainability in the textile industry. Within this aim, an in‐depth literature review on barriers was conducted by covering all supply chain stages and circular initiatives in textile industry. Then, a focus group study was implemented. In the focus group study, barriers related to supply chains that prevent companies to implement the circular economy were discussed and validated. As a result, a total of 25 barriers were classified under nine main categories such as (a) management and decision‐making, (b) labour, (c) design challenges, (d) materials, (e) rules and regulations, (f) lack of knowledge and awareness, (g) lack of integration and collaboration, (h) cost, and (i) technical infrastructure.